Twoje ja oddzwoni za chwilę. Wpływ nowych technologii na tożsamość i zakres autonomii działań - Albin, Krzysztof (My University, 2009)
The article is focused on the problems of the interaction between Self,Self-concepts and Self-believes with the IT objects. In reference to the views of Self by William James, Russell Belk, Hazel Markus and Alvin Toffler the research described below give the picture of change in Self structure among the Polish internet users. The intensive impact between the Self-concepts and IT technology is still getting stronger. The most important results:1. Over 1/5 subjects, users of the mobile phone and Internet, treat the mobile phone as the part of their Self-indentity. 2. 11% subjects treat the mobile phone as the part of their Self and without of this part the existence is impossible at all. 3. 18% subjects, treat the memory and data of the mobile phone the same as the personal memory. The contacts with IT objects, especially the mobile phone, lead to the change of autonomy of Self-perception and planning of everyday activity. The research described In the article are the second stage of research and lead to the next ones dedicated to more close examination of described below effects. The influence of IT technology to the Self structure is still getting stronger. The specific direction of the influence is difficult to close prediction in this moment, but in opinion of author-must be monitored and described. Because of geometrie inerease of the intensity of the contact between the human being and the IT objects the forms the activity easy-to-do until today could be impossible to manage without of the IT support. For example in first stage of the research, made with IDI methodology, the subjects declare the lack of the chance of meeting with friends in the downtown without support of the mobile phone. From the other hand the strong positive impact between the IT technology and cognhwe abilities are undeniable in behavior in abstract level activity. In the opinion of author the name »mobile phone« is not actual in Polish culture anymore. This IT object should be treated as the »input« to the virtual data system.

Systematyczne i częste korzystanie z narzędzi technologicznych powoduje zmianę strategii działania, wpływa na jego sprawność, a po dłuższym czasie tworzy trwałe postawy wobec często wykorzystywanego narzędzia. Kiedy cechy urządzenia IT zostają zinterioryzowane może nastąpić akomodacja strategii działania użytkownika do uwarunkowań związanych z wykorzystywaną technologią, w sytuacji w której asymilacja cech tego narzędzia jest niemożliwa ze względu na ich znaczną złożoność. W efekcie może prowadzić to do zmian struktury Ja takiej osoby i wpływać na jej tożsamość.Z jednej strony proces ten zwiększa zakres Ja Poszerzonego użytkownika, z drugiej natomiast może ograniczać zakres autonomii jego działania. Zarówno sytuacjach o złożonej strukturze, jak i tych, które dotąd postrzegano jako proste i nie wymagające wparcia ze strony urządzeń zewnętrznych. Telefon komórkowy jest przez część respondentów, użytkowników Internetu, określany jako aspekt własnej tożsamości, a nawet jako »część siebie, bez której nie da się naprawdę żyć« Zasoby informacyjne telefonu komórkowego stają się też substytutem własnej pamięci, który staje się niezbędny w coraz większej ilości sytuacji. Sposób wykorzystania telefonu komórkowego przez respondentów wskazuje na skokową zmianę jego istotnych funkcji. Jest on raczej łączem z obszarem technologii wirtualnej, niż telefonem w klasycznym rozumieniu tego słowa. W świetle wyników badań można postawić tezę o rosnącej fetyszyzacji telefonu komórkowego, co jest w istotny sposób procesem głębszym niż klasyczna personifikacja obiektu. Zjawisko to jest w pewnym stopniu analogiczne do zmian, jakie następowały przy wprowadzeniu do obiegu kulturowego takich technologii jak druk w okresie Reformacji lub telewizji w latach 50. XX wieku.
Your self calls you back in one moment. The pressure of it technology to the identity and social behavior
Studia Humanistyczne AGH
Keywords: identity; identity transfer into IT objects; authonomy self; tożsamość; przesunięcie tożsamości w obiekt nowej technologii; self expended; autonomia ja; ja poszerzone; self level of behavior control; poziom kontroli działania